LIBRARIANS INFORMATION COMMUNICATION TECHNOLOGY SKILLS AS CORRELATE OF PRESERVATION AND CONSERVATION OF INFORMATION RESOURCES IN UNIVERSITY LIBRARIES IN DELTA AND EDO STATE (NAU Journal of Library and Information Science, 2023)
The study examined the correlation between librarians’ Information Communication Technology (ICT) skills and the preservation and conservation of information resources in university libraries across Delta and Edo States, Nigeria. Employing a correlational surveydesign, data were collected from 183 librarians using questionnaires and analyzed through descriptive and inferential statistics. Results revealed a high level of preservation and conservation of library resources in the university libraries, alongside a similarly high level ofICT skills among librarians. Furthermore, a significant relationship was established between librarians' ICT skills and the preservation and conservation efforts. While ICT facilitates preservation and conservation processes, it was noted that librarians must possess adequate ICT skills to effectively utilize electronic resources for this purpose. The study concluded that preservation and conservation efforts in these libraries are commendable, and changes in librarians' ICT skills could impact preservation outcomes. Recommendations include intensifying efforts to preserve and conserve library resources to meet user needs effectively.
Keywords: Librarians, ICT, ICT Skills, Preservation, Conservation, Information Resources, University Libraries, Edo, Delta.